ANALISIS PENGARUH WINGLET PADA SAYAP PESAWAT T-34C-1 DENGAN VARIASI SUDUT TEKUK MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS. - Riskiati Ihsani, (2022)
The increase in fuel prices has an impact on the world of aviation, which causes many parties to try to improve fuel efficiency by increasing flight effectiveness. As one of the innovations made with modifications on the wings, such as winglets. A Winglet is an additional device that is put on the wingtip to reduce the vortex and increase lift. This research discussed the effect of winglet addition with variations of cant angle on the wings of the T-34C-1 aircraft to lift and drag forces in cruise conditions. The research was conducted using a numerical simulation approach by varying the winglet cant angle were 15°, 30°, 45°,60°, 75° at constant speed and calculating fuel efficiency after winglet addition using the Breguet equation. The simulation results indicated that the wing with winglets produced the best performance at an angle of attack of 9° while the wing without winglets produced the best performance at an angle of attack 3°. From the CL and CD data analysis, it was known that winglet addition effected induced drag decrease to 53% and the fuel efficiency that happened increased from 57.9% as the highest increase and 6.72% as the lowest increase in fuel. Based on the results of the research, it can be concluded that winglet addition on aircraft wings affects aerodynamic efficiency, fuel efficiency and the level of induced drag on the wings.